Persistence in Breast Cancer Disparities Between African Americans and Whites in Wisconsin - Lepeak, Lisa (2011)
BACKGROUND: Breast cancer (BC) mortality is higher in African American women compared to white women despite having a lower incidence. The reasons for this remain unclear, despite decades of research. Reducing BC health disparities is a priority but has had limited success. OBJECTIVE: To assess progress in eliminating breast cancer-related health disparities in Wisconsin by comparing trends in breast cancer outcomes in African American and white women from 1995 to 2006 and comparing results nationally. METHODS: Age-adjusted breast cancer (BC) incidence and stage data from the Wisconsin Cancer Reporting System and age-adjusted mortality data from National Center of Health Statistics were used to evaluate trends in incidence and mortality from 1995 to 2006 for African Americans and whites. The relative disparity was evaluated by rate ratios. Trends in distribution of in situ versus malignant disease were examined. National trend data were obtained from the Nationa Cancer Institute (NCI) Surveillance, Epidemiology and End Results (SEER) database. RESULTS: Age-adjusted incidence decreased 10% in Wisconsin compared to 7% nationally. Incidence of BC was lower in African American compared to white women. BC mortality in African American women declined in Wisconsin, but remained higher than white females. Age-adjusted mortality in Wisconsin declined approximately 23%, matching national trends. Non age-adjusted stage data trended toward a decrease in malignant, but increased in situ disease. CONCLUSIONS: Despite an overall reduction in BC mortality from 1995 to 2006, a persistent disparity in mortality remains for African American women, demonstrating no significant progress in reducing BC health disparities.